A vision of European biogas sector development towards 2030: Trends and challenges. (10th March 2021) - Brémond, Ulysse; Bertrandias, Aude; Steyer, Jean-Philippe; Bernet, Nicolas; Carrere, Hélène
Abstract: The future European "Green Deal" will set ambitious greenhouse gas emissions reduction by 2030. Reaching these targets will partly rely on the decarbonization of the gas sector and the development of the biomethane. In this context, this article aims to provide a vision of the European biogas sector development from 2020 towards 2030 and beyond. It appears that the biogas sector is facing a shift in its development paradigm. Indeed, this sector is still mainly dominated by a model based on energy crops, high feed-in tariffs and local electrical production via combined heat and power units. However, biogas sector is now moving towards a different model, where organic wastes, agricultural by-products as well as sequential crops are mainly used as feedstocks, biogas is upgraded to biomethane for various applications (transportation, chemical production, heat, etc.) and subsidy schemes are progressively reduced. Overall, current European policies are pushing the sector to increase its sustainability and to reduce biogas production costs. To answer these challenges, the main improvement tracks are identified and discussed. In the future, it is believed that the biogas sector should address these aspects to ensure its growth towards 2030 and beyond. Graphical abstract: Image 1 Highlights: Over the last 20 years, European biogas sector has experienced a strong growth. Development paradigm of the biogas sector is currently shifting. Higher sustainability & cost production reduction are required by European policies. Biomethane production and the use of waste/sequential crops are now preferred. Additional sources of revenues (e.g. CO2 valorization) will develop in the future.